Potassium channels in the sinoatrial node and their role in heart rate control. Issue 1 (1st January 2018) - Aziz, Qadeer; Li, Yiwen; Tinker, Andrew
ABSTRACT: Potassium currents determine the resting membrane potential and govern repolarisation in cardiac myocytes. Here, we review the various currents in the sinoatrial node focussing on their molecular and cellular properties and their role in pacemaking and heart rate control. We also describe how our recent finding of a novel ATP-sensitive potassium channel population in these cells fits into this picture.